Pre-soil fumigation with ammonium bicarbonate and lime modulates the rhizosphere microbiome to mitigate clubroot disease in Chinese cabbage - Zhang, Jinhao; Zhou, Xinghai; Zhang, Yu; Dai, Zhenlin; He, Zulei; Qiu, Yue; Alharbi, Sulaiman Ali; Wei, Fangjun; Wei, Lanfang; Ahmed, Waqar; Ji, Guanghai (Frontiers in Microbiology, 2024)
Background: Plasmodiophora brassicae is an ever-increasing threat to cruciferous crop production worldwide. Aims and methods: This study investigated the impact of pre-soil fumigation with ammonium bicarbonate (N) and lime (NB) to manage clubroot disease in Chinese cabbage through 16S rRNA gene amplification sequencing. Results:We found that soil fumigation with N and NB suppressed disease incidence by reducing the soil acidity and population of P. brassicae in the rhizosphere. Minimum disease incidence and maximum relative control effect of about 74.68% and 66.28% were achieved in greenhouse and field experiments, respectively, under the combined application of ammonium bicarbonate and lime (LNB) as compared with N, NB, and control (GZ). Microbial diversity analysis through Miseq sequencing proved that presoil fumigation with N, NB, and LNB clearly manipulated rhizosphere microbial community composition and changed the diversity and structure of rhizosphere microbes compared with GZ. Bacterial phyla such as Proteobacteria, Bacteriodetes, and Acidobacteria and fungal phyla including Olpidiomycota and Ascomycota were most dominant in the rhizosphere of Chinese cabbage plants. Soil fumigation with N and NB significantly reduced the abundance of clubroot pathogen at genus (Plasmodiophora) level compared with GZ, while decreased further under combined application LNB.Microbial co-occurrence network analysis showed a highly connected and complex network and less computation competition for resources among microbes under combined application LNB. Conclusions: We conclude that for environmentally friendly and sustainable agriculture, soil fumigation with combined ammonium bicarbonate and lime plays a key crucial role in mitigating Chinese cabbage clubroot disease by alleviating soil pH, reducing pathogen population, and manipulating the rhizosphere microbiome.